2010
DOI: 10.2147/vaat.s6413
|View full text |Cite
|
Sign up to set email alerts
|

The next generation: etravirine in the treatment of HIV-1 infection in adults refractory to other antiretrovirals

Abstract: Etravirine is a second-generation nonnucleoside reverse transcriptase inhibitor (NNRTI) that is approved for the treatment of adult human immunodeficiency virus (HIV)-infected patients with documented or suspected resistance to first-generation NNRTIs. Etravirine has a flexible molecular structure that allows it to retain its activity against mutant HIV strains that exhibit resistance to first-generation agents. It is evident that 3 or more etravirine resistance-associated mutations are typically necessary bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Importantly, the difference in observations may be attributed to differences in measuring drug content versus NP content. Rapid burst release of ETR from the NP into the lumen and the propensity of ETR to bind proteins in vaginal fluid (as has been seen in plasma [56,57]) may have contributed to the lower drug content observed in vaginal tissues. To evaluate if ETR burst released before reaching vaginal tissue, we measured the in vitro release from ETR-NP under sink conditions and found that >95% of drug had released within 2 h (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the difference in observations may be attributed to differences in measuring drug content versus NP content. Rapid burst release of ETR from the NP into the lumen and the propensity of ETR to bind proteins in vaginal fluid (as has been seen in plasma [56,57]) may have contributed to the lower drug content observed in vaginal tissues. To evaluate if ETR burst released before reaching vaginal tissue, we measured the in vitro release from ETR-NP under sink conditions and found that >95% of drug had released within 2 h (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%